MODEL INTEGRASI STEM DAN TURATS DALAM MANAJEMEN KURIKULUM PESANTREN - Nashrullah Nashrullah; Rian Nur Farezi; Fionaldo Satria Devangga; Abdul Hamid (An-Nadzir : Jurnal Manajemen Pendidikan Islam, 2026)
This study examines in depth the holistic-integrative curriculum management model at MTs Pondok Mambaus Sholihin, which aims to synergize modern STEM literacy (scientific, technological, engineering, and mathematical reasoning competencies) with classical Islamic studies or turats (the treasury of religious scholarship rooted in the study of classical texts/kitab kuning). Pesantren-based madrasahs frequently confront epistemic dichotomies and the risk of cognitive overload among santri (Islamic boarding school students) when integrating secular and religious disciplines. Employing a field-based qualitative case study design, data were gathered through participant observation, in-depth interviews with institutional leadership and teaching staff, and a comprehensive document analysis of the Learning Objectives Flow. The findings of this study reveal that curriculum integration is precisely engineered at the planning stage through a "Convergent Curriculum" policy, which explicitly maps the intersections of cross-disciplinary Learning Outcomes (Capaian Pembelajaran/CP) to mitigate cognitive load. At the implementation level, the institution adopts an autonomy-supportive pedagogical approach aligned with the framework of Self-Determination Theory (SDT), effectively fostering intrinsic motivation, self-efficacy, and resilience among santri against academic burnout. Furthermore, the institutional quality assurance paradigm is reoriented by establishing adab (ethics) and akhlaqul karimah (noble character) as the absolute ontological foundation, ensuring that scientific advancement remains subordinate to spiritual and moral formation. Ultimately, this study confirms that precise managerial planning and an SDT-informed pedagogy successfully bridge secular and religious epistemologies, thereby offering a replicable framework for curriculum governance in Islamic educational institutions as they navigate the demands of Society 5.0.